World War II spies : an interactive history adventure - Burgan, Michael (North Mankato, Minn. : Capstone Press, 2013)
"Describes the role spies played during World War II. Readers' choices reveal various historical details"--
The secret keepers -- Resisting the enemy -- Spying for the other side -- Behind enemy lines -- Espionage at war.
Includes bibliographical references (p. 111) and index.
Keywords: World War, 1939-1945 -- Secret service -- Juvenile literature; Espionage -- History -- 20th century -- Juvenile literature; Spies -- History -- 20th century -- Juvenile literature